Effect of gelatin stabilized copper nanopeprintss on catalytic reduction of methylene blue - Musa, Aminu; Ahmad @ Ayob, Mansor; Hussein, Mohd. Zobir; Saiman, Mohd Izham; Abubakar Sani, Hannatu (SpringerOpen, 2016)
The synthesis of copper nanoparticles was carried out with gelatin as a stabilizer by reducing CuSO4.5H2O ions using hydrazine. Ascorbic acid and aqueous NaOH were also used as an antioxidant and pH controller, respectively. The effects of NaOH, hydrazine, and concentration of gelatin as stabilizer were studied. The synthesized copper nanoparticles were characterized by UV-vis spectroscopy, XRD, zeta potential measurements, FTIR, EDX, FESEM, and TEM. The formation of CuNPs@Gelatin is initially confirmed by UV-vis spectroscopic analysis with the characteristic band at 583 nm. XRD and TEM reports revealed that CuNPs@Gelatin (0.75 wt.%) is highly crystalline and spherical in shape with optimum average size of 4.21 ± 0.95 nm. FTIR studies indicated the presence of amide group on the surface of the CuNPs indicating the stability of CuNPs which is further supported by zeta potential measurements with the negative optimum value of −37.90 ± 0.6 mV. The CuNPs@G4 showed a good catalytic activity against methylene blue (MB) reduction using NaBH4 as a reducing agent in an aqueous solution. The best enhanced properties of CuNPs@G4 were found for the 0.75 wt.% gelatin concentration. Thermodynamic parameters (ΔH and ΔS) indicate that under the studied temperature, the reduction of MB by CuNPs@G4 is not feasible and had endothermic in nature.